2017
DOI: 10.1007/s40596-017-0706-4
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Patients in a Behavioral Medicine Massive Open Online Course (MOOC): A Qualitative and Quantitative Analysis of Participants’ Perceptions

Abstract: ObjectiveThe purpose of this article is to explore learners’ perceptions of using virtual patients in a behavioral medicine Massive Open Online Course (MOOCs) and thereby describe innovative ways of disseminating knowledge in health-related areas.MethodsA 5-week MOOC on behavioral medicine was hosted on the edX platform. The authors developed two branched virtual patients consisting of video recordings of a live standardized patient, with multiple clinical decision points and narration unfolding depending on l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(30 citation statements)
references
References 30 publications
1
25
0
4
Order By: Relevance
“…This is in line with prior research results, which demonstrate high participants' satisfaction when engaging with VPs in MOOCs [11]. Nineteen percent (19%) of the total participants dropped out from the exercise, of which the bulk of these participants dropped out without starting the VP (76% of dropouts).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…This is in line with prior research results, which demonstrate high participants' satisfaction when engaging with VPs in MOOCs [11]. Nineteen percent (19%) of the total participants dropped out from the exercise, of which the bulk of these participants dropped out without starting the VP (76% of dropouts).…”
Section: Discussionsupporting
confidence: 90%
“…VPs have been previously introduced in MOOCs to increase levels of interactivity of learners with the MOOC content [9,10]. In one study, the results indicated that the VPs were perceived as a helpful exercise in the course by 83.1% of the responding participants (n = 442) [11]. Other positive outcomes of MOOCs using VPs was seen in a Urology MOOC which had a higher overall student completion rate 10.4% compared to the reported 5% average completion in MOOCs [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most medical MOOCs include assessments consisting of automatically graded multiple choice quizzes and exams, automated or peerassessed short open-ended questions, and open question that require a long answer such as a reflection or an essay (Reilly et al 2014). Also, virtual patients and educational games are being used for assessing learners on clinical reasoning skills (Stathakarou et al 2014;Subhi et al 2014;Reinders and de Jong 2016;Berman et al 2017). Formal MOOC assessments usually include a combination of assessment modes, and for the integration into your course it is up to you if the MOOC assessment of your choice counts as a high or low stake assessment.…”
Section: Tipmentioning
confidence: 99%
“…WBME is gaining increasing acceptance through activities and courses offered by Virtual Learning Environments (VLEs). These spaces help minimize problems in the classroom, such as material availability, since it is a form of self-directed and potentially interactive study carried out at different times and places, but focused on the same content and same skills 6,7 .…”
Section: Contextomentioning
confidence: 99%